Resistance Training and Elite Athletes: A Systematic Bibliometric Analysis (2015–2023) - Wiria Dinata, Windo; Fitri, Mustika; Mukhtarsyaf, Fahd; Rifki, Muhamad Sazeli (Physical Education Theory and Methodology, 2026)
Objectives. This study aims to systematically map global research trends, influential contributors, and thematic evolution in resistance training (RT) research involving elite athletes from 2015 to 2023. Materials and Methods. A systematic bibliometric analysis was conducted using the Scopus database. Study selection followed PRISMA 2020 guidelines and focused on RT interventions involving elite competitive populations. Duplicate records were removed, followed by title, abstract, and full-text screening conducted by independent reviewers. VOSviewer version 1.6.20 was used to generate bibliometric visualizations, including co-authorship, co-citation, and keyword co-occurrence networks. Key bibliometric indicators, such as publication trends, citation impact, collaboration networks, and thematic clustering, were evaluated. Results. From an initial total of 2,710 records, 678 documents met the eligibility criteria. Global scientific productivity exhibited steady growth, with a marked acceleration after 2019. The United States demonstrated the highest citation impact, whereas Spain and Brazil emerged as central international collaboration hubs. Three major thematic clusters were identified: (1) performance optimization strategies, including velocity-based training and blood flow restriction; (2) neuromuscular adaptations and hypertrophy mechanisms; and (3) youth athlete development with increasing integration of digital and monitoring technologies. Conclusions. Research on RT in elite athletes continues to expand, characterized by strong international collaboration and increasing methodological refinement. The findings emphasize the central role of RT in high-performance sport and provide directions for future research, particularly regarding gender inclusivity, advanced monitoring technologies, and standardized measurement approaches.